2007
DOI: 10.1097/01.shk.0000246903.40142.aa
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Do Not Protect Against the Lethal Effects of Experimental Heatstroke in Baboons

Abstract: The mortality and neurological morbidity in heatstroke have been attributed to the host's inflammatory responses to heat stress, suggesting that anti-inflammatory therapy may improve outcome. We tested the hypothesis that a high dose of dexamethasone protects baboons against the lethal effects of heatstroke. Ten anesthetized baboons (Papio hamadryas) were assigned randomly to dexamethasone (n = 5) or control group (n = 5). Dexamethasone (2 mg/kg i.v.) was administered in four divided doses every 6 h starting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 26 publications
1
30
1
Order By: Relevance
“…In contrast, an experiment in a baboon heat stroke model suggested that glucocorticoid did not reduce mortality [14]. Although there are no available data in humans, we think that hydrocortisone was effective to improve an infl ammatory imbalance in our patient.…”
Section: Discussioncontrasting
confidence: 60%
“…In contrast, an experiment in a baboon heat stroke model suggested that glucocorticoid did not reduce mortality [14]. Although there are no available data in humans, we think that hydrocortisone was effective to improve an infl ammatory imbalance in our patient.…”
Section: Discussioncontrasting
confidence: 60%
“…Neutralizing studies in animal models of heatstroke have established that this systemic inflammation has a significant role but it remains unclear whether it is beneficial or deleterious. As shown previously, inhibition of the inflammatory response with administration of IL-1 receptor antagonist [8], anti-inflammatory steroids [12] or recombinant activated protein C [7], [10] prevented organ damage and improved survival while other studies using IL-6 and tumor necrosis factor (TNF) receptors knockout mice [9] or primate models [11] reported enhanced mortality. One of the reasons that might explain these conflicting findings is that the molecular mechanisms that initiate and propagate the inflammatory response to heat stress are not known, although earlier studies have suggested that lipopolysaccharide (LPS) leaking into the systemic circulation from heat damaged gut is the primary stimulus [3], [9].…”
Section: Introductionmentioning
confidence: 70%
“…Clinical and experimental studies consistently demonstrated the presence of a systemic inflammatory response to heat stress that correlated with severity and outcome [5], [6], [7], [8], [9], [10], [11], [12]. Neutralizing studies in animal models of heatstroke have established that this systemic inflammation has a significant role but it remains unclear whether it is beneficial or deleterious.…”
Section: Introductionmentioning
confidence: 99%
“…No pharmacological treatment has been found to be beneficial. Antipyretics have no role in heat stroke and may be toxic to the liver, whereas experimental findings in a primate classic heat stroke model do not support the clinical use of corticosteroids or activated protein C in the prevention or treatment of classic heat stroke (48,49).…”
Section: Treatmentmentioning
confidence: 97%